Lithium iron phosphate positive electrode material, preparation method thereof and electrochemical device

By introducing lithium fluoride into the lithium iron phosphate positive electrode material and adopting specific grinding and sintering processes, the problem of insufficient low-temperature performance and energy density of the material is solved, and the improvement of the rate performance, low-temperature performance and compaction density of the material is achieved.

CN119852378APending Publication Date: 2025-04-18NANTONG RESHINE NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510112117.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The low-temperature performance and energy density of lithium iron phosphate positive electrode materials limit their large-scale applications.

Method used

By introducing a certain amount of lithium fluoride into the matrix material and cladding layer of the lithium iron phosphate positive electrode material, and combining the grinding process and two sintering processes, a conductive network is built to improve the conductivity and structural stability of the material.

Benefits of technology

The rate performance, low-temperature performance and compaction density of lithium iron phosphate positive electrode material are improved, and the synchronous improvement of energy density, rate performance and low-temperature performance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852378A_ABST
    Figure CN119852378A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material, a preparation method thereof and an electrochemical device, the preparation method comprises the following steps: mixing a phosphorus source, an iron source, a lithium source, a first carbon source, lithium fluoride, a first additive and a solvent to form a primary mixed material, and carrying out primary sintering to obtain a matrix material, the mass percentage M of the lithium fluoride accounting for the total mass of the iron source and the phosphorus source being 0-0.1%; the matrix material, a second carbon source, lithium fluoride, a second additive and a solvent are mixed to form a secondary mixed material, the mass percent N of the lithium fluoride added in the step in the total mass of the iron source and the phosphorus source is 0-0.3%, and N and M are not 0 at the same time; and grinding the secondary mixed material to obtain a secondary mixed material A and a secondary mixed material B with different particle sizes, and carrying out mixing and secondary sintering to obtain the lithium iron phosphate positive electrode material with good compaction density, rate capability and low-temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new energy materials, and in particular to a lithium iron phosphate positive electrode material, a preparation method thereof, and an electrochemical device. Background Art

[0002] Lithium-ion batteries are increasingly being used in various fields due to their excellent high energy density. The cathode materials of lithium-ion batteries generally use lithium cobalt oxide, ternary materials, lithium manganese oxide and lithium iron phosphate. Among them, lithium iron phosphate cathode materials have become one of the most popular cathode materials due to their advantages such as high safety performance, low price, stable chemical structure and long cycle life.

[0003] However, in practical applications, lithium iron phosphate positive electrode materials have poor low-temperature performance and low energy density, which limits the large-scale application of lithium iron phosphate positive electrode materials. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material.

[0005] The embodiments of the present application also provide a lithium iron phosphate positive electrode material prepared by the above-mentioned method for preparing the lithium iron phosphate positive electrode material, and an electrochemical device using the lithium iron phosphate positive electrode material.

[0006] In a first aspect, an embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material, comprising: Mixing a phosphorus source, an iron source, a lithium source, a first carbon source, lithium fluoride, a first additive and a first solvent to form a primary mixture, grinding the primary mixture and performing a primary sintering to obtain a matrix material, wherein the mass percentage M of the lithium fluoride to the total mass of the iron source and the phosphorus source is 0-0.1%; Mixing the base material, the second carbon source, lithium fluoride, the second additive and the second solvent to form a secondary mixed material, wherein the mass percentage N of the lithium fluoride added in this step to the base material is 0-0.3%, and N and M are not 0 at the same time; and The secondary mixed material is ground to obtain a secondary mixed material A with a particle size D50 of 0.6 μm to 1.0 μm and a secondary mixed material B with a particle size D50 of 0.2 μm to 0.4 μm. The secondary mixed material A and the secondary mixed material B are mixed and subjected to secondary sintering to obtain the lithium iron phosphate positive electrode material.

[0007] In some possible embodiments, the secondary mixed material A and the secondary mixed material B are mixed in a mass ratio of (20-80):(80-20).

[0008] In some possible embodiments, the step of grinding the secondary mixed material further includes: Grinding the secondary mixed material for the first time to obtain the secondary mixed material A, wherein the diameter of the grinding beads used in the first grinding is 0.6 mm to 1.0 mm; and A portion of the secondary mixed material A is ground for the second time to obtain the secondary mixed material B, and the diameter of the grinding beads used in the second grinding is 0.2 mm to 0.35 mm.

[0009] In some possible embodiments, the step of grinding the primary mixed material further includes: The primary mixed material is ground for the first time until the particle size D50 is 1.5 μm~3.0 μm, and then ground for the second time until the particle size D50 is 0.8 μm~1.3 μm, the diameter of the grinding beads used in the first grinding is 0.6 mm~1.0 mm, and the diameter of the grinding beads used in the second grinding is 0.2 mm~0.35 mm.

[0010] In some possible embodiments, the primary sintering temperature is 450° C. to 750° C., and the primary sintering time is 3 h to 15 h; and / or The temperature of the secondary sintering is 600° C. to 780° C., and the time of the secondary sintering is 3 h to 15 h.

[0011] In some possible embodiments, in the primary mixed material, the molar ratio of phosphorus in the phosphorus source, iron in the iron source and lithium in the lithium source is P:Fe:Li (1.015-1.036):1:(1.0-1.04).

[0012] In some possible embodiments, the first additive and the second additive are independently selected from at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide and niobium pentoxide.

[0013] In some possible embodiments, the compaction density of the lithium iron phosphate positive electrode material under a pressure of 150 MPa is ≥ 2.5 g / cm 3 ; and / or The powder resistivity of the lithium iron phosphate positive electrode material under a pressure of 150 MPa is ≤45Ω·cm.

[0014] In a second aspect, an embodiment of the present application provides a lithium iron phosphate positive electrode material prepared by the aforementioned method for preparing a lithium iron phosphate positive electrode material, wherein the lithium iron phosphate positive electrode material comprises a base material and a coating layer, and at least one of the base material and the coating layer contains lithium fluoride.

[0015] In a third aspect, an embodiment of the present application provides an electrochemical device, which includes a positive electrode plate, and the positive electrode plate includes a positive electrode active material, and the positive electrode active material is the aforementioned lithium iron phosphate positive electrode material.

[0016] Compared with the prior art, the lithium iron phosphate positive electrode material provided in the embodiment of the present application introduces a certain amount of lithium fluoride into at least one of the matrix material and the coating layer, that is, the lithium iron phosphate is bulk doped with lithium fluoride, or surface coated, or doping and coating are combined. Since lithium fluoride has good electronic conductivity and ionic conductivity, it can improve the electronic conductivity and ion transfer rate of the lithium iron phosphate positive electrode material, reduce the internal resistance of the lithium iron phosphate positive electrode material at low temperature and high rate, thereby improving the rate performance and low temperature performance of the lithium iron phosphate positive electrode material.

[0017] Secondly, by grinding the secondary mixed material, lithium fluoride can be more evenly distributed on the surface or between the crystal lattices of lithium iron phosphate, thereby further improving the conductivity of the lithium iron phosphate positive electrode material; in the grinding process, particles of different sizes are further obtained to achieve particle size grading, thereby increasing the compaction density of the lithium iron phosphate positive electrode material and improving the problem of decreased compaction density caused by the introduction of lithium fluoride.

[0018] In addition, a two-time sintering preparation process is adopted. First, a solid-phase reaction between the raw materials is carried out through a primary sintering, and carbon thermal reduction is utilized to form a matrix material having a lithium iron phosphate crystal phase. Then, a secondary sintering is performed to carbon-coat the surface of the matrix material. This reduces the free carbon generated by the fusion of lithium salts in the primary sintering and improves the carbon coating effect. Lithium fluoride can work together with the carbon coating layer to construct a conductive network.

[0019] The embodiments of the present application can effectively improve the conductivity of the positive electrode material, improve the particle size distribution, build a conductive network and improve the structural stability through the synergistic effect of lithium fluoride doping and / or coating with the grinding process and the double sintering process, thereby achieving a joint improvement in the rate performance, low temperature performance and compaction density of the lithium iron phosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A process flow chart of a method for preparing a lithium iron phosphate positive electrode material provided in one embodiment of the present application.

[0021] Figure 2 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material in Example 1 of the present application.

[0022] Figure 3 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material in Example 2 of the present application.

[0023] Figure 4 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material in Comparative Example 1 of the present application.

[0024] Figure 5 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material in Comparative Example 3 of the present application. DETAILED DESCRIPTION

[0025] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0026] See also Figure 1 As shown, the present application embodiment provides a method for preparing a lithium iron phosphate positive electrode material, which specifically includes the following steps: Step S1, mixing a phosphorus source, an iron source, a lithium source, a first carbon source, lithium fluoride, a first additive and a first solvent to form a primary mixture, grinding the primary mixture and performing a sintering to obtain a matrix material, wherein the mass percentage M of lithium fluoride to the total mass of the iron source and the phosphorus source is 0-0.1%.

[0027] In this step, a primary mixture is formed by mixing the raw materials of a phosphorus source, an iron source, a lithium source, a first carbon source, lithium fluoride, a first additive and a first solvent in a certain proportion. Exemplarily, the first solvent may be water. The primary mixture is then ground to make the primary mixture evenly mixed and the particles refined. The ground primary mixture is sintered once, a solid phase reaction is carried out between the raw materials, and carbon thermal reduction is performed to form a matrix material having a lithium iron phosphate crystal phase, and lithium fluoride is uniformly doped and distributed in the matrix material. The doping of lithium fluoride in this step helps to improve the electronic and ionic conductivity of the lithium iron phosphate positive electrode material, and enhance the rate performance and low temperature performance of the lithium iron phosphate positive electrode material.

[0028] Among them, the mass percentage M of the lithium fluoride added in step S1 to the total mass of the iron source and the phosphorus source is 0~0.1%. By controlling the doping amount of lithium fluoride in the lithium iron phosphate positive electrode material within the aforementioned range, the situation in which the compaction density of the lithium iron phosphate positive electrode material is reduced due to excessive lithium fluoride doping (M is greater than 0.1%) and the particle size grading effect is deteriorated can be reduced. In addition, in this step, lithium fluoride may not be doped. M can illustratively be 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1% or any value within the range composed of any two of the above values. M can further be 0.02%~0.1%.

[0029] The first carbon source may account for 5% to 7% of the total mass of the iron source and the phosphorus source, which is conducive to the solid phase reaction and reduces the generation of free carbon. Specifically, the first carbon source may include at least one of glucose, sucrose, starch, and polyethylene glycol.

[0030] The lithium source, iron source and phosphorus source can be added according to the molar ratio of the elements, Li:Fe:P=(1.0~1.04):1:(1.015~1.036).

[0031] In some embodiments, the phosphorus source includes at least one of ferric phosphate, phosphoric acid, lithium dihydrogen phosphate, monoammonium phosphate, and diammonium phosphate, etc. The phosphorus source may further be ferric phosphate.

[0032] In some embodiments, the iron source includes at least one of ferric phosphate, ferric oxide, ferroferric oxide, and ferric hydroxide. The iron source may further be ferric phosphate.

[0033] In some embodiments, the lithium source may include at least one of lithium dihydrogen phosphate, lithium carbonate, and lithium hydroxide.

[0034] In some embodiments, the first additive may include at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide, and niobium pentoxide, etc. Doping the first additive can effectively improve the crystal structure, electronic conductivity, ionic conductivity, thermal stability, and compactness of the matrix material, and further improve the rate performance and low temperature performance of the lithium iron phosphate cathode material.

[0035] In some embodiments, the mixing method may include mixing with a high-speed mixer, stirring or grinding, etc. It is understandable that the mixing method includes but is not limited to the above methods.

[0036] In some embodiments, grinding the primary mixed material may include: using grinding beads with a diameter of 0.6 mm to 1.0 mm to perform a first grinding (i.e., coarse grinding) of the primary mixed material to a particle size D50 of 1.5 μm to 3.0 μm, quickly reducing the particle size and improving the mixing uniformity between the raw materials; and then using grinding beads with a diameter of 0.2 mm to 0.35 mm to perform a first grinding (i.e., fine grinding) to a particle size D50 of 0.8 μm to 1.3 μm, further refining the particle size and making the particle size distribution of the primary mixed material more uniform. Adopting step-by-step grinding, i.e., a grinding method combining coarse grinding and fine grinding, is conducive to improving grinding efficiency and improving particle size distribution.

[0037] In some embodiments, the primary sintering temperature is 450°C to 750°C, and the primary sintering temperature within the above range is conducive to the formation of lithium iron phosphate crystal phase. The primary sintering temperature can be 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or any value within the range formed by any two of the above values. Further, the primary sintering temperature can be 500°C to 750°C.

[0038] In some embodiments, the time of the primary sintering can be 3h to 15h, which is conducive to the full reaction of the raw materials. The time of the primary sintering can be 3h, 5h, 5h, 10h, 12h, 14h, 15h or any value within the range of any two of the above values. The time of the primary sintering can further be 7h to 10h.

[0039] In some embodiments, the heating rate of the primary sintering may be 2° C. / min to 5° C. / min, which is beneficial to the uniformity of the solid phase reaction and reduces the thermal stress and structural defects caused by rapid heating.

[0040] In some embodiments, the primary sintering atmosphere may be an inert atmosphere to avoid oxidation of metal elements in the primary mixed material and improve the crystal structure integrity and chemical composition stability of the matrix material.

[0041] In some embodiments, the sintering equipment for primary sintering may include one of a push plate kiln, a roller kiln, and a rotary kiln.

[0042] In some embodiments, before the primary mixed material is subjected to the primary sintering, the primary mixed material may be spray dried, which helps to quickly convert the liquid primary mixed material into a uniform powder, and is conducive to the uniform reaction of the primary mixed material during the primary sintering process. The inlet air temperature of the spray drying may be 200°C to 270°C, and the outlet air temperature may be 85°C to 100°C.

[0043] Step S2, mixing the base material, the second carbon source, lithium fluoride, the second additive and the second solvent to form a secondary mixed material, wherein the mass percentage N of lithium fluoride added in this step to the base material is 0-0.3%, and N and M are not 0 at the same time.

[0044] In this step, the base material, the second carbon source, lithium fluoride, the second additive and the second solvent are mixed to form a secondary mixed material. Exemplarily, the second solvent can be water. In this step, lithium fluoride is added again, and lithium fluoride and the second carbon source are coated on the surface of the base material, which helps to improve the electronic and ionic conductivity of the lithium iron phosphate positive electrode material and enhance the rate performance and low temperature performance of the lithium iron phosphate positive electrode material. Lithium fluoride coating can also effectively reduce the erosion of the lithium iron phosphate positive electrode material by the electrolyte and reduce the dissolution of metal ions. The lithium fluoride in the coating layer helps to promote the formation of a stable and dense positive electrode electrolyte interface film (CEI), which is beneficial to improve the stability of the acid iron lithium positive electrode material and the electrolyte interface, thereby improving the electrochemical performance of the acid iron lithium positive electrode material.

[0045] Among them, the mass percentage N of lithium fluoride added in step S2 to the matrix material is 0~0.3%. By controlling the coating amount of lithium fluoride within the aforementioned range, it is beneficial to reduce the reduction in the compaction density of the lithium iron phosphate positive electrode material caused by excessive lithium fluoride coating (N is greater than 0.3%) and the deterioration of the particle size grading effect. In addition, in this step, lithium fluoride may not be coated. N can be illustratively 0, 0.001%, 0.005%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3% or any value within the range composed of any two of the above values. N can further be 0.01%~0.3%.

[0046] It can be understood that if M and N are not 0 at the same time, lithium fluoride can be added only in step S1 to dope the bulk phase of the matrix material with lithium fluoride; lithium fluoride can be added only in step S2 to coat the surface of the matrix material; lithium fluoride can also be added in both step S1 and step S2 to achieve a combination of bulk doping and surface coating. The above three schemes can improve the low temperature performance and rate performance of lithium iron phosphate positive electrode materials.

[0047] In some embodiments, the second carbon source may include at least one of glucose, sucrose, starch, polyethylene glycol, etc. Further, the second carbon source may be a mixture of glucose and polyethylene glycol.

[0048] In some embodiments, the second carbon source may account for 3% to 14% of the mass of the matrix material, which is conducive to moderate carbon coating on the surface of the matrix material. Exemplarily, the second carbon source is a mixture of glucose and polyethylene glycol, wherein glucose accounts for 2.0% to 7.0% of the mass of the matrix material, and polyethylene glycol accounts for 1.0% to 7.0% of the mass of the matrix material.

[0049] In some embodiments, the second additive may include at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide, and niobium pentoxide, etc. Coating the second additive can further improve the rate performance and low temperature performance of the lithium iron phosphate positive electrode material.

[0050] Step S3, grinding the secondary mixed material to obtain a secondary mixed material A with a particle size D50 of 0.6 μm to 1.0 μm and a secondary mixed material B with a particle size D50 of 0.2 μm to 0.4 μm, mixing the secondary mixed material A and the secondary mixed material B and performing secondary sintering to obtain a lithium iron phosphate positive electrode material.

[0051] The present application adds lithium fluoride in the aforementioned steps S1 and S2 to improve the low temperature performance and rate performance of the lithium iron phosphate positive electrode material. However, during the experiment, the inventors of the present application found that the addition of lithium fluoride would lead to a decrease in the compaction density of the lithium iron phosphate positive electrode material, which may be related to the lower density of lithium fluoride, gas release during sintering, compatibility differences between lithium fluoride and lithium iron phosphate materials, and the impact on the particle morphology of the lithium iron phosphate positive electrode material. To this end, the present application combines a special grinding process to improve the lithium iron phosphate positive electrode material, so that the large and small particles can be graded, so that small particles can fill the gaps between large particles, thereby improving the compaction density of the lithium iron phosphate positive electrode material, so as to take into account the comprehensive improvement of the energy density, low temperature performance and rate performance of the lithium iron phosphate positive electrode material.

[0052] Specifically, the grinding includes: using grinding beads with a diameter of 0.6mm~1.0mm to perform a first grinding (i.e., coarse grinding) on ​​the secondary mixed material to obtain a secondary mixed material A with a particle size D50 of 0.6μm~1.0μm; then using grinding beads with a diameter of 0.2mm~0.35mm to perform a second grinding (i.e., fine grinding) on ​​part of the secondary mixed material A to obtain a secondary mixed material B with a particle size D50 of 0.2μm~0.4μm.

[0053] After grinding, the secondary mixture A and the secondary mixture B with different particle sizes are mixed and the particle size is graded so that the small particles can fill the gaps between the large particles, thereby improving the compaction density of the lithium iron phosphate positive electrode material. The mixing method may include mixing, stirring or grinding with a high-speed mixer. It is understood that the mixing method includes but is not limited to the above method. The mixing time can be 0.5h~3h, which is conducive to sufficient mixing.

[0054] Among them, the secondary mixed material A and the secondary mixed material B can be mixed in a mass ratio of (20~80): (80~20). The mixing ratio will affect the number distribution of large and small particles in the primary particles in the lithium iron phosphate positive electrode material product, and then affect the compaction density and electrochemical performance of the lithium iron phosphate positive electrode material. When there are too many large particles (secondary mixed material A), there is a lack of small particles to fill the gaps, and the compaction density of the lithium iron phosphate positive electrode material is not improved enough. In addition, due to the excessive number of large particles, the electron migration path is lengthened, and the rate performance will also decrease. When there are too many small particles (secondary mixed material B), the number of large particles is too small, the number of gaps is reduced, and the compaction density will also decrease. In addition, due to the excessive number of small particles, the specific surface area of ​​the lithium iron phosphate positive electrode material is too large, which will cause the increase of the internal resistance and surface side reactions of the lithium iron phosphate positive electrode material. Therefore, controlling the mass ratio of the secondary mixed material A and the secondary mixed material B to (20~80): (80~20) is conducive to the simultaneous improvement of the compaction density and electrochemical performance of the lithium iron phosphate positive electrode material. The mass ratio of the secondary mixed material A to the secondary mixed material B may further be (60-40): (40-60).

[0055] In some embodiments, the temperature of the secondary sintering is 600°C to 780°C, and the secondary sintering temperature within the above range is conducive to the coating of lithium fluoride, the second carbon source and the second additive, and reduces the free carbon produced by the fusion of lithium salts in the primary sintering process, resulting in poor carbon coating. The temperature of the secondary sintering can be 600°C, 650°C, 700°C, 750°C, 780°C or any value within the range composed of any two of the above values. Further, the temperature of the secondary sintering can be 700°C to 780°C. The time of the secondary sintering can be 3h to 15h, which is conducive to full sintering. The time of the secondary sintering can be 3h, 5h, 5h, 10h, 12h, 14h, 15h or any value within the range composed of any two of the above values. The time of the secondary sintering can further be 7h to 10h.

[0056] In some embodiments, the heating rate of the secondary sintering may be 2° C. / min to 5° C. / min, which is beneficial for reducing thermal stress and structural defects caused by rapid heating.

[0057] In some embodiments, the atmosphere of the secondary sintering can be an inert atmosphere, which is beneficial to reduce the oxidation of metal elements in the lithium iron phosphate positive electrode material and improve the crystal structure integrity and chemical composition stability of the lithium iron phosphate positive electrode material.

[0058] In some embodiments, the sintering equipment for the secondary sintering may include one of a push plate kiln, a roller kiln, and a rotary kiln.

[0059] In some embodiments, before the secondary mixed material A and the secondary mixed material B are subjected to secondary sintering, the secondary mixed material A and the secondary mixed material B may be spray dried, which is conducive to uniform secondary sintering. The inlet air temperature of the spray drying may be 200°C to 270°C, and the outlet air temperature may be 85°C to 100°C.

[0060] In some embodiments, the powder resistivity of the lithium iron phosphate cathode material at a pressure of 150 MPa is ≤45 Ω·cm, and lithium fluoride improves the electronic conductivity and ionic conductivity of the lithium iron phosphate cathode material, effectively reducing the internal resistance of the lithium iron phosphate cathode material. The powder resistivity of the lithium iron phosphate cathode material at a pressure of 150 MPa can further be 20 Ω·cm~35 Ω·cm.

[0061] In some embodiments, the compaction density of the lithium iron phosphate positive electrode material at a pressure of 150 MPa is ≥ 2.5 g / cm 3 The grinding of the secondary mixed material achieves the particle size distribution of large and small particles, which effectively improves the compaction density of the lithium iron phosphate cathode material. The compaction density of the lithium iron phosphate cathode material under a pressure of 150Mpa can be further 2.5g / cm 3 ~2.6g / cm 3 .

[0062] Compared with the prior art, the preparation method of the lithium iron phosphate positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. By doping lithium iron phosphate with a certain amount of lithium fluoride in the bulk phase, or coating the surface, or combining doping with coating, the electronic conductivity and ion transfer rate of the lithium iron phosphate positive electrode material can be effectively improved, thereby improving the rate performance and low temperature performance of the lithium iron phosphate positive electrode material.

[0063] 2. Combined with the grinding process, the secondary mixed material is ground to achieve particle size distribution, reduce the reduction in compaction density caused by lithium fluoride, and achieve a simultaneous improvement in the energy density, rate performance and low-temperature performance of lithium iron phosphate positive electrode materials.

[0064] 3. The preparation method is simple, efficient, and environmentally friendly, which is conducive to the large-scale production of lithium iron phosphate positive electrode materials and has excellent commercial prospects.

[0065] The present application also provides a lithium iron phosphate positive electrode material prepared by the above-mentioned preparation method of the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material includes a base material and a coating layer, and at least one of the base material and the coating layer contains lithium fluoride.

[0066] Compared with the prior art, due to the introduction of a certain amount of lithium fluoride into at least one of the base material and the coating layer, and the use of a unique grinding process, the electronic conductivity and ion transfer rate of the lithium iron phosphate positive electrode material are improved, the internal resistance under high rate and low temperature conditions is reduced, and the compaction density of the lithium iron phosphate positive electrode material is also improved. Therefore, the lithium iron phosphate positive electrode material provided in the embodiment of the present application has good energy density, rate performance and low temperature performance.

[0067] An embodiment of the present application further provides an electrochemical device (eg, a battery), which includes a positive electrode plate, wherein the positive electrode plate includes a positive electrode active material, and the positive electrode active material is the lithium iron phosphate positive electrode material as described above.

[0068] The electrochemical device prepared using the aforementioned lithium iron phosphate positive electrode material has the advantages of high capacity, high rate performance and good low temperature performance, and can be used under low temperature conditions.

[0069] The above-mentioned lithium iron phosphate positive electrode material, its preparation method and electrochemical device are further described below through specific examples.

[0070] Example 1 Step S1, 6kg glucose, 525.5g titanium dioxide, 25kg lithium carbonate, 100kg iron phosphate, 44g lithium fluoride and 142kg water are mixed evenly, wherein the molar ratio of Li:Fe:P is 1.039:1:1.032, and a primary mixture is obtained, wherein the mass percentage M of the added lithium fluoride to the iron phosphate (phosphorus source and iron source) is 0.044% (addition amount). The primary mixture is introduced into a sand mill for the first grinding (coarse grinding, zirconium bead diameter 0.6mm) to a particle size of D50=1.86μm, and then introduced into a sand mill for the second grinding (fine grinding, zirconium bead diameter 0.3mm) to a particle size of D50=1.0μm. Then spray drying is performed, and the spray drying air inlet temperature is 220℃ and the air outlet temperature is 90℃. The dried primary mixture is heated to 650°C at a rate of 2.5°C / min under an inert atmosphere, kept at that temperature for 7.5 hours for primary sintering, and cooled to obtain a matrix material.

[0071] Step S2: 100 kg of the base material, 3.5 kg of glucose, 6.0 kg of polyethylene glycol (molecular weight 6000), 166.8 g of titanium dioxide and 136 kg of water are mixed and stirred uniformly to obtain a secondary mixture.

[0072] Step S3, introduce the secondary mixed material into a sand mill for the first grinding (coarse grinding, zirconium bead diameter 0.6mm) to obtain a secondary mixed material A with a particle size of D50=0.78μm, and then grind part of the secondary mixed material A for the second time (fine grinding, zirconium bead diameter 0.3mm) to obtain a secondary mixed material B with a particle size of D50=0.36μm. Mix the secondary mixed material A and the secondary mixed material B in a mass ratio of 50:50. Spray dry the mixture, the spray drying inlet temperature is 220℃, and the outlet temperature is 90℃. The dried mixture is raised to 750℃ at a rate of 2.5℃ / min under inert atmosphere protection conditions, kept warm for 7.5h for secondary sintering, cooled, air flow crushed, sieved, and iron removed to obtain a lithium iron phosphate positive electrode material.

[0073] Example 2 The difference from Example 1 is that: in step S1, lithium fluoride is not added, that is, M is 0, and in step S2, lithium fluoride is added to the secondary mixture, and the mass percentage N of the added lithium fluoride to the base material is 0.1%. The other steps are basically the same as in Example 1, please refer to Example 1.

[0074] Example 3 The difference from Example 2 is that in step S2, the mass percentage N of lithium fluoride added to the base material is 0.3%. The other steps are basically the same as Example 2, please refer to Example 2.

[0075] Example 4 The difference from Example 1 is that in step S1, the mass percentage M of lithium fluoride in iron phosphate (phosphorus source and iron source) is 0.02%. The other steps are basically the same as Example 1, please refer to Example 1.

[0076] Example 5 The difference from Example 1 is that in step S1, the mass percentage M of lithium fluoride in iron phosphate (phosphorus source and iron source) is 0.1%. The other steps are basically the same as Example 1, please refer to Example 1.

[0077] Example 6 The difference from Example 1 is that: in step S2, lithium fluoride is added to the secondary mixed material, and the mass percentage N of the added lithium fluoride to the base material is 0.3%. The other steps are basically the same as Example 1, please refer to Example 1.

[0078] Comparative Example 1 Step S1, 8.5kg glucose, 2.6kg polyethylene glycol (molecular weight 6000), 525.5g titanium dioxide, 25kg lithium carbonate, 100kg iron phosphate and 142kg water are mixed evenly, wherein the molar ratio of Li:Fe:P is 1.039:1:1.032, to obtain a mixture, the mixture is introduced into a sand mill for coarse grinding (zirconium bead diameter 0.6mm) to a particle size of D50 = 1.86μm, and then introduced into a sand mill for fine grinding (zirconium bead diameter 0.3mm) to a particle size of D50 = 0.46μm. Then spray drying is performed, the spray drying air inlet temperature is 220℃, and the air outlet temperature is 90℃. The dried mixture is heated to 780℃ at a rate of 2.5℃ / min under inert atmosphere protection conditions, and sintered for 7.5h. After cooling, air flow crushing, sieving, and iron removal, lithium iron phosphate positive electrode material is obtained.

[0079] Comparative Example 2 The difference from Comparative Example 1 is that: in step S1, lithium fluoride is added to the mixture, and the mass percentage of the added lithium fluoride to the iron phosphate (phosphorus source and iron source) is 0.044%. The other steps are basically the same as those in Comparative Example 1, please refer to Comparative Example 1.

[0080] Comparative Example 3 The difference from Example 1 is that in step S1, the mass percentage M of lithium fluoride in iron phosphate (phosphorus source and iron source) is 0. The other steps are basically the same as those in Example 1, please refer to Example 1.

[0081] Comparative Example 4 The difference from Example 1 is that in step S1, the mass percentage M of lithium fluoride in iron phosphate (phosphorus source and iron source) is 0.15%. The other steps are basically the same as Example 1, please refer to Example 1.

[0082] Comparative Example 5 The difference from Example 1 is that: in step S1, lithium fluoride is not added in step S1, that is, M is 0; in step S2, the mass percentage N of lithium fluoride in iron phosphate (phosphorus source and iron source) is 0.5%. The other steps are basically the same as in Example 1, please refer to Example 1.

[0083] The lithium iron phosphate positive electrode materials obtained in Examples 1-6 and Comparative Examples 1-5 were tested accordingly.

[0084] Test method: 1. Field emission scanning electron microscope (SEM) test: Thermo Fisher's AxiaChemiSEMHiVac scanning electron microscope was used. This instrument has high-resolution imaging capabilities and can clearly observe the microscopic morphology and structural characteristics of the positive electrode material. The acceleration voltage is 10.00 kV, the working distance is 10 mm, and the magnification is 10,000 times.

[0085] 2. Carbon content determination: The infrared analysis method is used to test the carbon content of the LFP positive electrode material. A carbon-sulfur analyzer is used to burn the sample under high temperature and oxygen-rich conditions. The carbon element contained in it is oxidized into carbon dioxide and enters the infrared detector with the carrier gas. The carbon content is calculated by quantitatively analyzing the changes in the intensity of the infrared absorption wavelength of the carbon dioxide signal.

[0086] 3. Determination of compaction density: Test according to the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals, "Determination of compaction density of lithium-ion battery positive electrode material powder".

[0087] 4. Resistivity determination: Test according to the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals, "Determination of Resistivity of Lithium-ion Battery Positive Electrode Material Powder".

[0088] 5. Electrochemical performance test: button cells were used for electrical performance testing. The above-mentioned positive electrode materials, polyvinylidene fluoride (PVDF), and conductive agents (such as acetylene black or conductive carbon black) were mixed in a mass ratio of 93:3.5:3.5, and an appropriate amount of NMP was added to form a slurry. Then, the slurry was evenly coated on aluminum foil, vacuum dried at 115℃±5℃ / 8h, compacted, and cut into discs. Metal lithium sheets were used as negative electrode materials, and finally transferred to the glove box to assemble into CR2025 button cells. The constant current charge and discharge test was performed using the Xinwei battery test system.

[0089] (I) Rate performance test: The test operating voltage range is 2.0V~3.75V, the temperature is 25℃, and the 0.1C gram capacity, first efficiency, and 1.0C gram capacity of the button battery are measured.

[0090] (ii) Low temperature performance test: The test operating voltage range is 2.0V~3.75V, the temperature is 25℃, and the 1.0C charging capacity of the button battery is measured; then the battery is transferred to -15℃, discharged to 2.0V, and the 1.0C discharge capacity of the button battery is measured to obtain the capacity retention rate relative to the 1.0C charging capacity at 25℃.

[0091] The relevant process parameters of Examples 1-6 and Comparative Examples 1-5 are shown in Table 1, and the relevant test results are shown in Table 2.

[0092] The above results show: The scanning electron microscopy results of the lithium iron phosphate positive electrode material prepared in Example 1 are as follows Figure 2 As shown, the scanning electron microscopy results of the lithium iron phosphate positive electrode material prepared in Example 2 are as follows Figure 3As shown, the scanning electron microscopy results of the lithium iron phosphate positive electrode material prepared in Comparative Example 1 are as follows Figure 4 As shown, the scanning electron microscopy results of the lithium iron phosphate positive electrode material prepared in Comparative Example 3 are as follows Figure 5 As shown. Figure 2-Figure 5 It can be seen that compared with the single sintering process of Comparative Example 1, Example 1 adopts a double sintering process, and the obtained lithium iron phosphate positive electrode material has a small particle size of 200nm~400nm, a large particle size of 1.0μm~1.3μm, and a large and small particle size gradation is achieved; while the lithium iron phosphate positive electrode material obtained in Comparative Example 1 has a small particle size of 300nm~500nm, a large particle size of 0.8μm~1.0μm, and a large and small particle size gradation is not obvious. Compared with Comparative Example 3, Examples 1 and 2 also mix slurries of different particle sizes in the secondary sand milling stage to achieve a large and small particle size gradation, and the compaction density of the lithium iron phosphate positive electrode material is improved.

[0093] As shown in Table 1 and Table 2, compared with Comparative Examples 1 and 2, Examples 1-6 have a higher compaction density, better rate performance, and better low-temperature performance because they combine grinding and step-by-step sintering processes to achieve particle size grading and sufficient lithium fluoride doping and / or coating. Compared with Comparative Example 3, after lithium fluoride doping and / or coating, Examples 1-6 have better rate performance and improved low-temperature performance.

[0094] Among them, compared with the lithium fluoride doped in Example 1-2, Example 3 can not only improve the rate performance and low-temperature performance of the lithium iron phosphate positive electrode material by coating with lithium fluoride, but also effectively protect the positive electrode from electrolyte corrosion and reduce metal dissolution. The lithium fluoride in the coating layer is conducive to the formation of a stable CEI, which is beneficial to improving the stability of the positive electrode and electrolyte interface, thereby improving the electrochemical performance of the lithium iron phosphate positive electrode material.

[0095] By comparing Example 1, Example 3 and Example 6, it is found that in Example 6, by adding lithium fluoride in both step S1 and step S2, that is, by simultaneously performing bulk doping and surface coating on the positive electrode material, the rate performance and low temperature performance of the lithium iron phosphate positive electrode material are further improved. However, due to the increase in the lithium fluoride content in the lithium iron phosphate positive electrode material, the compaction density of the lithium iron phosphate positive electrode material decreases.

[0096] By comparing Example 1, Example 4, Example 5 and Comparative Example 4, it can be seen that as the amount of lithium fluoride added in step S1 increases, that is, the amount of lithium fluoride doped increases, the rate performance and low-temperature discharge capacity of the lithium iron phosphate positive electrode material are improved. When the addition amount M reaches 0.044% (Example 5), the 0.1C charging capacity of the lithium iron phosphate positive electrode material is as high as 162.0mAh / g, but the compaction density decreases slightly. When the addition amount M is too high, reaching 0.15% (Comparative Example 4), the compaction density, rate performance and low-temperature discharge capacity of the lithium iron phosphate positive electrode material all decrease.

[0097] Comparison of Example 2, Example 3 and Comparative Example 5 shows that as the amount of lithium fluoride added in step S2 increases, that is, the amount of lithium fluoride coated increases, the rate performance and low-temperature discharge capacity of the lithium iron phosphate positive electrode material are improved. When the addition amount N reaches 0.3% (Example 3), the resistivity of the lithium iron phosphate positive electrode material is only 22Ω·cm, the 1C discharge capacity is increased to 150.2mAh / g, the discharge capacity at low temperature is also increased to 112.8 mAh / g, and the volume retention rate is also 70.0%. When the addition amount N is too high, reaching 0.50% (Comparative Example 5), the rate performance and low-temperature discharge capacity of the lithium iron phosphate positive electrode material are reduced, and the compaction density is significantly reduced.

[0098] It can be seen that by doping a certain amount of lithium fluoride in the bulk phase, or by surface coating, or by combining doping and coating, and combining a unique grinding process and sintering process, the lithium iron phosphate positive electrode material can exhibit ideal compaction density, energy density, rate performance and low temperature performance.

[0099] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: include: Mixing a phosphorus source, an iron source, a lithium source, a first carbon source, lithium fluoride, a first additive and a first solvent to form a primary mixture, grinding the primary mixture and performing a primary sintering to obtain a matrix material, wherein the mass percentage M of the lithium fluoride to the total mass of the iron source and the phosphorus source is 0-0.1%; Mixing the base material, the second carbon source, lithium fluoride, the second additive and the second solvent to form a secondary mixed material, wherein the mass percentage N of the lithium fluoride added in this step to the base material is 0-0.3%, and N and M are not 0 at the same time; and The secondary mixed material is ground to obtain a secondary mixed material A with a particle size D50 of 0.6 μm to 1.0 μm and a secondary mixed material B with a particle size D50 of 0.2 μm to 0.4 μm. The secondary mixed material A and the secondary mixed material B are mixed and subjected to secondary sintering to obtain the lithium iron phosphate positive electrode material.

2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The secondary mixed material A and the secondary mixed material B are mixed in a mass ratio of (20-80):(80-20).

3. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step of grinding the secondary mixed material, the method further comprises: Grinding the secondary mixed material for the first time to obtain the secondary mixed material A, wherein the diameter of the grinding beads used in the first grinding is 0.6 mm to 1.0 mm; and A portion of the secondary mixed material A is ground for the second time to obtain the secondary mixed material B, and the diameter of the grinding beads used in the second grinding is 0.2 mm to 0.35 mm.

4. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step of grinding the primary mixed material, the method further comprises: The primary mixed material is ground for the first time until the particle size D50 is 1.5 μm~3.0 μm, and then ground for the second time until the particle size D50 is 0.8 μm~1.3 μm, the diameter of the grinding beads used in the first grinding is 0.6 mm~1.0 mm, and the diameter of the grinding beads used in the second grinding is 0.2 mm~0.35 mm.

5. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The primary sintering temperature is 450° C. to 750° C., and the primary sintering time is 3 h to 15 h; and / or The temperature of the secondary sintering is 600° C. to 780° C., and the time of the secondary sintering is 3 h to 15 h.

6. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the primary mixed material, the molar ratio of phosphorus in the phosphorus source, iron in the iron source and lithium in the lithium source is (1.015-1.036):1:(1.0-1.04).

7. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The first additive and the second additive are independently selected from at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide and niobium pentoxide.

8. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The compaction density of the lithium iron phosphate positive electrode material under a pressure of 150 MPa is ≥ 2.5 g / cm 3 ; and / or The powder resistivity of the lithium iron phosphate positive electrode material under a pressure of 150 MPa is ≤45Ω·cm.

9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 8, and the lithium iron phosphate positive electrode material comprises a base material and a coating layer, and at least one of the base material and the coating layer contains lithium fluoride.

10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material, and the positive electrode active material is the lithium iron phosphate positive electrode material as described in claim 9.

Citation Information

Patent Citations

  • Synthesis method of high-purity fluorine-doped lithium iron phosphate anode material

    CN101867041A

  • Fluorinion-doped lithium iron phosphate material and preparation methods thereof

    CN102024951A

  • Preparation method of lithium iron phosphate material

    CN112599768A

  • Lithium iron phosphate positive electrode material and preparation method and application thereof

    CN118373397A

Cited By

  • Modified lithium iron phosphate as well as preparation method and application thereof

    CN119725520A

  • Lithium iron phosphate positive electrode material and preparation method therefor, and electrochemical device

    WO2026157291A1